ANALISA PENERAPAN PERHITUNGAN REKONSILIASI FISKAL TERHADAP LAPORAN KEUANGAN KOMERSIAL PADA PT XYZ - Dariansyah, Deddy (Politeknik Negeri Jakarta, 2018)
ABSTRACT LAPORAN KEUANGAN KOMERSIAL PADA PT XYZ Deddy Dariansyah Universitas IndraPrasta PGRIdeddyjogjazz@yahoo.co.id The calculation of fiscal reconciliation made by the company (taxpayer) due to differences in calculations,especially profit by commercial accounting and taxable profit (fiscal). to bridge the existence of differences incommercial financial statements and fiscal financial statements for more efficient then fiscal Financial Statementsprepared in tandem with commercial financial statements, meaning that although commercial or business financialstatements are prepared on the basis of business accounting principles, but the provision of taxation is dominantin the process of reporting the preparation of reports finance. The causes of differences in commercial financialstatements and fiscal financial statements are due to differences in accounting principles, accounting methods andprocedures, differences in income and expense recognition, as well as differences in income and expensetreatment.. In addressing the differences that occur between the Commercial Income Statement and the FiscalIncome Statement, based on the Financial Accounting Standards and the applicable tax law, based on the resultsof research and calculation analysis of the calculation of fiscal reconciliation to the Financial Statement of profit.Keywords : Reconciliation Fiscal, Financial Statement, Tax Law